1998
DOI: 10.1111/1467-9876.00106
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric and Non-Linear Models and Data Mining in time Series: A Case-Study on the Canadian Lynx Data

Abstract: Nonparametric regression methods are used as exploratory tools for formulating, identifying and estimating non-linear models for the Canadian lynx data, which have attained benchmark status in the time series literature since the work of Moran in 1953. To avoid the curse of dimensionality in the nonparametric analysis of this short series with 114 observations, we con®ne attention to the restricted class of additive and projection pursuit regression (PPR) models and rely on the estimated prediction error varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The data set has 114 observations, corresponding to the period of 1821-1934. It has also been extensively analyzed in the time series literature with a focus on the nonlinear modeling (Campbell & Walker, 1977;Cornillon, Imam, & Matzner, 2008;Lin & Pourahmadi, 1998;Tang & Ghosal, 2007) see Wong and Li (2000) for a survey. Following other studies (Subba Rao & Sabr, 1984;Stone & He, 2007;Zhang, 2003), the logarithms (to the base 10) of the data are used in the analysis.…”
Section: The Canadian Lynx Series Forecastsmentioning
confidence: 99%
“…The data set has 114 observations, corresponding to the period of 1821-1934. It has also been extensively analyzed in the time series literature with a focus on the nonlinear modeling (Campbell & Walker, 1977;Cornillon, Imam, & Matzner, 2008;Lin & Pourahmadi, 1998;Tang & Ghosal, 2007) see Wong and Li (2000) for a survey. Following other studies (Subba Rao & Sabr, 1984;Stone & He, 2007;Zhang, 2003), the logarithms (to the base 10) of the data are used in the analysis.…”
Section: The Canadian Lynx Series Forecastsmentioning
confidence: 99%
“…The snapshots whose projections are too far from the true measurements are inconsistent with the data and should not be used. This is similar to the cross validation widely used in statistical model selection literature [ Lin and Pourahadi , 1998]. The main difference is that magnetospheric tomographic imaging is an ill‐conditioned inverse problem with few path‐integrated measurements, while the statistical model selection is a well‐conditioned but overdetermined problem.…”
Section: Magnetospheric Image Reconstructionmentioning
confidence: 84%
“…Based on the average of these 12 absolute prediction errors (AAPE), FAR(2,2) performs slightly better than SETAR (2). Other nonparametric time series models for the Canadian lynx data include the projection pursuit regression (PPR) model fitted by Lin and Pourahmadi [36] who found that SETAR outperforms PPR in terms of one-step-ahead forecasts, and neural network models which Kajitani, Hipel and McLeod [25] found to be "just as good or better than SETAR models for one-step out-of-sample forecasting of the lynx data. "…”
Section: Application To the 1821-1934 Canadian Lynx Datamentioning
confidence: 99%